Efektivitas penyembuhan luka bakar menggunakan salep ekstrak etanol daun ciplukan (Physalis angulata L.) pada kelinci - Cindy Marlina Tambunan; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Rafita Yuniarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Indonesian people have long used plants as medicine and for health maintenance, which is inherited from generation to generation. One plant that can be used in traditional medicine is the ciplukan plant (Physalis angulata L.), which is a small plant that can grow anywhere. It turns out not only has a unique taste but is also beneficial for health; ciplukan can be used to treat flu and sore throat, whooping cough, bronchitis, mumps, ulcers, and also Ayan or epilepsy. Empirically, the use of ciplukan plants functions as a cure for smallpox, which has been used by the community by bathing. Smallpox is shaped like a blistered burn and will be shaped like an ulcer. So, researchers are interested in developing in the form of ointment because it is more effective to use and can be taken anywhere. This research was conducted to determine that ethanol extract of ciplukan leaves can be formulated on the basis of absorbent ointment and to determine the healing effect of burns in rabbits from the preparation of ethanol extract ointment of ciplukan leaves (Physalis angulata L.). Ciplukan leaf extract is made from simplicial ciplukan leaves by maceration method and then tested for the effectiveness of healing burns on rabbits using ointment. The ointment is made in 4 formulations, namely F0, F1 (10%), F2 (15%), and F3 (20%) using white Vaseline as the ointment base. Evaluation of ointment preparations includes physical stability (shape, smell and colour, homogeneity, pH, dispersion, adhesion and viscosity. All formulas of ointment preparations are good in storage. In ointment preparations in the homogeneity test, all formulas are homogeneous. In pH inspection, dispersion, adhesion and viscosity all meet requirements according to predetermined or established standards. Ciplukan leaf extract can be formulated into an ointment dosage form. Ointment preparations with a high concentration are most effective in healing burns in rabbits.